A COMPARATIVE STUDY ON GROWTH, CARCASS TRAITS AND BODY COMPOSITION OF AWASSI AND KARADI LAMBS RAISED UNDER TWO LEVELS OF FEEDING AND SLAUGHTERED AT DIFFERENT WEIGHTS: 2- BODY COMPOSITION AND CARCASS TISSUE DISTRIBUTION - Al-Sherwany, D. A. O.; Alkass, J. E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A total of 32 weaned (3.5-4 months) of Awassi (16) and Karadi (16) lambs were randomly allocated into two equal groups to be fed either ad libitum or 3% of their body weight concentrate, and to be slaughtered at 36 and 44 kg body weight. After chilling at 40c for 24h, the carcass was split along the vertebral column into two halves by electric saw, and the left side was separated into eight whole sale cuts and were physically dissected into lean, fat and bone and weighed. Results reveal that the overall mean of lean, fat, bone, lean: fat and lean: bone ratio were 60.31±0.25%, 17.05± 0.69%, 22.63 ± 0.59%, 3.78 ±0.20 and 2.71 ± 0.06, respectively. It was noticed that Karadi lambs surpass significantly (P<0.01) Awassi lambs in the content of lean (61.32±0.29 vs. 59.30±0.21%) and bone (24.72±0.85 vs. 20.53±0.35%) and had lower content of fat (13.94±0.75 vs. 20.15±0.39%). Neither lambs fed ad libitum nor 3% concentrate had a significant effect on composition of the carcasses. Lambs slaughtered at 44 kg had significantly (P<0.01) higher content of fat and lower bone content. Awassi lambs and those slaughtered at 44 kg had significantly (P<0.01) higher total body fat than did Karadi lambs and those slaughtered at 36 kg.